2021
DOI: 10.5812/jkums.114001
|View full text |Cite
|
Sign up to set email alerts
|

The Periodontal Status of Pregnant and Lactating Women in Ilam Province, Iran (2018 - 2019)

Abstract: Background: Gingivitis and periodontitis cause the inflammation of the soft tissue around the teeth and destroy the supporting structures of the teeth. This is highly prevalent during pregnancy and lactation. Objectives: The present study aimed to investigate the periodontal status in pregnant and lactating women in Ilam province, Iran in 2018 - 2019. Methods: This descriptive-analytical study was conducted on 100 pregnant and lactating women who were selected via cluster and stratified sampling. Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The low prevalence rate in the Gesase study could have been influenced by the location of the study (in an urban area with good education). 14 According to the results of the present study, BOP and dental calculus observed in pregnant women were 17% and 36.4% respectively, that were consistent with the studies in Iran by Meybodi, 37 Dehghanipour 31 , Taheri 30 , Abdal 29 and also in other countries. 34,38 However, the rates of BOP in the study by Lasisi 23 in Nigeria and by Wandera 24 in Uganda were significantly lower (5.2% and 3.3%, respectively).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The low prevalence rate in the Gesase study could have been influenced by the location of the study (in an urban area with good education). 14 According to the results of the present study, BOP and dental calculus observed in pregnant women were 17% and 36.4% respectively, that were consistent with the studies in Iran by Meybodi, 37 Dehghanipour 31 , Taheri 30 , Abdal 29 and also in other countries. 34,38 However, the rates of BOP in the study by Lasisi 23 in Nigeria and by Wandera 24 in Uganda were significantly lower (5.2% and 3.3%, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…24 In Abdal's study, among pregnant women in Ilam, according to the CPTIN index, 70% received code>0 (Healthy gum=30%, bleeding on probing=18%, calculus=36%, and periodontal pocket (4-5mm)=16%). 29 The Gesase's study among 1117 pregnant women in Tanzania showed the 14.2% prevalence of gum disease using CPI (code>0). The low prevalence rate in the Gesase study could have been influenced by the location of the study (in an urban area with good education).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on pregnant women in the city of Arak, Iran, it was indicated that 55.4% of pregnant women had periodontal disease, and brushing frequency was the main predictor of gum health [ 12 ]. In another study in the city of Ilam, Iran, it was reported that in total, 30% of pregnant women had healthy gums, and 18% of them had bleeding gums [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Iran's study showed a maximum number of pregnant women with healthy gingiva in contrast to the current study. 10,25 The barriers to utilisation of orodental care among pregnant women were characterised by different themes, including lack of dental education, no dental insurance, dental anxiety, self-neglect, oral health beliefs, refusal from the dentist, no suitable dentist, previous bad experiences, dental costs, time constraints, and the stress of pregnancy. Different studies have highlighted barriers to the utilisation of orodental care, which is quite similar to the current study findings.…”
Section: Discussionmentioning
confidence: 99%